2016
DOI: 10.1167/iovs.16-20082
|View full text |Cite
|
Sign up to set email alerts
|

Inner Retinal Oxygen Delivery, Metabolism, and Extraction Fraction in Ins2Akita Diabetic Mice

Abstract: PurposeRetinal nonperfusion and hypoxia are important factors in human diabetic retinopathy, and these presumably inhibit energy production and lead to cell death. The purpose of this study was to elucidate the effect of diabetes on inner retinal oxygen delivery and metabolism in a mouse model of diabetes.MethodsPhosphorescence lifetime and blood flow imaging were performed in spontaneously diabetic Ins2Akita (n = 22) and nondiabetic (n = 22) mice at 12 and 24 weeks of age to measure retinal arterial (O2A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…A graphical summary, classified by imaging technique, is given in Figure 11. Our value of mean diameter of primary vessels matches that of the in vivo slit lamp biomicroscope (Blair et al, 2016) study and is within the range reported by ex vivo scanning electron microscopy (Ninomiya & Inomata, 2006). However, the diameters reported by intravital microscopy studies (Harris et al, 2013; Lee & Harris, 2008; Z.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A graphical summary, classified by imaging technique, is given in Figure 11. Our value of mean diameter of primary vessels matches that of the in vivo slit lamp biomicroscope (Blair et al, 2016) study and is within the range reported by ex vivo scanning electron microscopy (Ninomiya & Inomata, 2006). However, the diameters reported by intravital microscopy studies (Harris et al, 2013; Lee & Harris, 2008; Z.…”
Section: Discussionsupporting
confidence: 87%
“…While investigating the mouse literature for normative values of diameter, velocity and flow in retinal vessels, we found that there is a paucity of such studies. To the best of our knowledge, we have counted all of fifteen journal papers which measure retinal blood velocity and/or flow in the living mouse eye (Blair et al, 2016; Harris, Watts, & Leskova, 2013; Lee & Harris, 2008; Liu et al, 2017; Muir, Rentería, & Duong, 2012; Z. Wang, Yadav, Leskova, & Harris, 2010, 2011; Watts, Eshaq, Carter, & Harris, 2013; Wright & Harris, 2008; Wright, Messina, & Harris, 2009; Wright, Singh Yadav, McElhatten, & Harris, 2012; Yadav & Harris, 2011; Zawadzki et al, 2015; Zhi et al, 2014, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Microelectrode measurements provide local values of retinal oxygen tension only. 45,46 Phosphorescence quenching measures retinal oxygen tension in retinal vessels, 56,57 and direct comparison with oxygen saturation measurements as obtained in the present study may be difficult. However, there are several studies indicating that the technique provides sufficiently valid measurements.…”
Section: Discussionmentioning
confidence: 75%
“…While investigating the mouse literature for normative values of diameter, velocity and flow in retinal vessels, we found, first, that there is a paucity of such studies. To the best of our knowledge, we have counted all of 15 journal papers which measure retinal blood velocity and/or flow in the living mouse eye (Blair et al, 2016; Harris et al, 2013; Lee and Harris, 2008; Liu et al, 2017; Muir et al, 2012; Wang et al, 2010; Wang et al, 2011; Watts et al, 2013; Wright and Harris, 2008; Wright et al, 2009; Wright et al, 2012; Yadav and Harris, 2011; Zawadzki et al, 2015; Zhi et al, 2014; Zhi et al, 2012). As stated earlier, all these studies measure velocity/flow only in the primary (first generation) vessels emerging from the optic disk.…”
Section: Discussionmentioning
confidence: 99%